(untitled) - Alonso, Alfonso (Washington, DC, 2000)
Contents: Biodiversity - The "Stuff of life"; Breakthroughs in conservation biology - Lessons from Camisea.
Keywords: Biological diversity,Biological diversity conservation,Đa dạng sinh học,Bảo tồn đa dạng sinh học